2020
DOI: 10.1016/j.jbusres.2019.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Customer deviance: A framework, prevention strategies, and opportunities for future research

Abstract: The phrase the "customer is always right" assumes that customers provide universal benefits for firms. However, in recent years, customer deviance is on the rise and the academic literature has provided little insight into the drivers of deviance, the actual behaviors, and strategies for how managers can better manage a customer base that cannot be classified as universally benign. This article addresses customer deviance ranging from classic examples like shoplifting to engaging in hostile to anti-brand behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 100 publications
1
79
0
Order By: Relevance
“…Not only did it add to their emotional stress, it at times led to violence. Consumer deviance has received attention in past research (Fombelle et al 2020), but again not in the presence of a market shock. Future research needs to understand both the short- and long-term impact that market shocks have on the mental and physical well-being of FLEs.…”
Section: Supporting Service Employees During a Market Shockmentioning
confidence: 99%
“…Not only did it add to their emotional stress, it at times led to violence. Consumer deviance has received attention in past research (Fombelle et al 2020), but again not in the presence of a market shock. Future research needs to understand both the short- and long-term impact that market shocks have on the mental and physical well-being of FLEs.…”
Section: Supporting Service Employees During a Market Shockmentioning
confidence: 99%
“…Literature from the management domain has examined how customer deviance behavior impacts firms, customers, and other customers. Fombelle et al (2020) proposes a customer deviance process framework that includes customer deviance triggers, customer deviance behaviors targeting, and customer deviance consequences, and customer prevention strategies to explain how consumers proactively engage in deviance behavior. Event scholars may consider customer deviance as a plausible framework to explain how attendees actively defy local or national ordinances and recommendations by public health officials to choose to meet and gather during the COVID-19 pandemic.…”
Section: Customer Deviancementioning
confidence: 99%
“…Although many service researchers have explored the positive aspects of C2C interactions in physical and virtual commercial and non-commercial service settings (e.g., Harris and Baron, 2004 ; Zeithaml et al, 2018 ), considerably fewer researchers have explored negative experiences from other customers and unacquainted strangers ( Fombelle et al, 2019 ; Nicholls, 2010 ). The reason for this research void may be that while managers can encourage C2C interactions by modifying consumption settings (e.g., furniture, open spaces, entertainment) or by encouraging the formation of social or online customer communities ( Libai et al, 2010 ), they are mostly powerless to stop negative C2C interactions that occur for brief moments ( Colm et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, many customer-to-customer studies have shown that negative service experiences are often benign intrusions or interruptions that often transpire when customers have to wait in queues together, converse with language difficulties, or when they have to share space with small children. However, sometimes, customer-to-customer incivility may also result in physical harm, or even death, ( Fombelle et al, 2019 ). In the following sections, this paper turns its attention to exploring customer-to-customer incivility that transpires in under-researched settings, i.e.…”
Section: Introductionmentioning
confidence: 99%